Software reuse in the emerging cloud computing era - Yang, Hongji; Liu, Xiaodong, 1966- (Information Science Reference, 2012)
"This book clarifies the present fast-advancing literature of the current state of art and knowledge in the areas of the development and reuse of reusable assets in emerging software systems and applications"--Provided by publisher
Keywords: Computer software -- Reusability.; Cloud computing.; Service-oriented architecture (Computer science); elektronické knihy; electronic books